Smokers’ beliefs about the tobacco control potential of “a gene for smoking”: a focus group study - Waters, Erika A (BMC Public Health, 2014)
BACKGROUND: Several genetic variations associated with nicotine dependence and lung cancer exist. Translating this knowledge into tobacco control policy relies on smokers’ perceptions of the implications of the research. This study explored smokers’ beliefs about the tobacco control uses for research examining genomics, smoking, and addiction. METHOD: Smokers (N = 85) participated in one of thirteen focus groups and one interview, stratified by race (eight black, six white) and education (seven < Bachelor’s degree, seven ≥ Bachelor’s degree). Data were analyzed by two independent coders using standard analysis and validation techniques. RESULTS: Nearly all groups suggested using genetic information for youth-oriented tobacco prevention education. Beliefs about the effectiveness of such actions varied. Many participants believed that providing smokers personalized genetic testing results or informing them about the existence of a gene would not motivate people to quit. All smokers emphasized the need for improved smoking cessation treatment options. Using genomics research to develop gene therapies and personalized drug treatments were also mentioned, yet perceptions of such treatments were mixed. Whereas some participants viewed the possibility positively, others expressed concern about cost and access. Participants who were skeptical of the effectiveness of using genetic information for tobacco control noted that the harms of tobacco use are widely known and genetic information does not add much of a deterrent. CONCLUSION: Participants generated several possible tobacco control uses for genomics research findings. Our findings suggest that tobacco control experts should consult with smokers prior to implementing tobacco control measures. The potential public health benefits of genetics and genomics research related to tobacco use cannot be realized until communication strategies that are most likely to encourage and support tobacco avoidance decisions, and minimize mistrust and backlash, are identified.